STRENGTHENING INDEPENDENT CURRICULUM IMPLEMENTATION THROUGH SCHOOL COMMITTEE AND TEACHER SYNERGY: A CASE STUDY AT MTS AR-RAHMAN MEROMBOK - Abdul Majir; Ismail Nasar; Robertus Hudin (Prima Magistra: Jurnal Ilmiah Kependidikan, 2025)
The successful implementation of the Independent Curriculum in Indonesian schools and madrasahs critically depends on the collaborative engagement of all educational stakeholders. Within this framework, school committees hold a strategic position, functioning as facilitators, advocates, supervisors, and intermediaries who contribute to ensuring the availability of essential facilities and fostering a conducive learning environment. This study investigates the strategic role of the school committee in supporting teacher preparedness for the implementation of the Independent Curriculum at MTs Ar-Rahman Merombok, Manggarai Barat. Framed within a qualitative research paradigm, data were collected through in-depth interviews, systematic observations, and document analysis to ensure methodological rigor and contextual relevance. The findings indicate that the school exhibits considerable institutional readiness for the curriculum transition, evidenced by robust committee involvement and a high degree of teacher comprehension regarding curricular objectives, competencies, and pedagogical frameworks. However, significant challenges remain, particularly concerning the adequacy of educational resources and teacher competence in conducting outcome-based assessments both of which are central to the curriculum's success. These results highlight the critical importance of sustained stakeholder collaboration, capacity-building initiatives, and strategic resource allocation to ensure effective and enduring educational reform. This study contributes to the growing body of knowledge on participatory governance in education and underscores the pivotal function of school committees in driving systemic transformation within Indonesia's evolving educational landscape.